2002
DOI: 10.1097/00004703-200204000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Firearm Safety to Children: Failure of a Program

Abstract: The present study investigated the effectiveness of a skills-based firearm safety program on reducing children's play with firearms. In a randomized control study, 34 children aged 4 to 7 years participated in a week-long firearm safety program; the Control Group was composed of 36 children. After the program, pairs of children were observed playing in a structured setting in which they had access to a semiautomatic pistol. A total of 53% of the pairs played with the gun, and there was no difference in gun-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 8 publications
0
35
0
1
Order By: Relevance
“…Although researchers have attempted to promote safe storage practices by gun owning parents, many parents continue to store their firearms unsafely (loaded and unlocked; Azrael, Miller, & Hemenway, 2000;Grossman, Reay, & Baker, 1999). In addition, Hardy (2002), Hardy, Armstrong, Martin, and Strawn (1996), and Jackman, Simon, Farah, and Kellerman (2001) have shown that when children find firearms, they are likely to play with them. Furthermore, Eber, Annest, Mercy, and Ryan (2004) reported that playing with firearms found in the home resulted in hundreds of deaths and thousands of injuries to children in the years 1993 to 2001.…”
Section: Behavioral Skills Training (Bst)mentioning
confidence: 99%
“…Although researchers have attempted to promote safe storage practices by gun owning parents, many parents continue to store their firearms unsafely (loaded and unlocked; Azrael, Miller, & Hemenway, 2000;Grossman, Reay, & Baker, 1999). In addition, Hardy (2002), Hardy, Armstrong, Martin, and Strawn (1996), and Jackman, Simon, Farah, and Kellerman (2001) have shown that when children find firearms, they are likely to play with them. Furthermore, Eber, Annest, Mercy, and Ryan (2004) reported that playing with firearms found in the home resulted in hundreds of deaths and thousands of injuries to children in the years 1993 to 2001.…”
Section: Behavioral Skills Training (Bst)mentioning
confidence: 99%
“…30 In stark contrast to parental expectations, controlled investigations have demon-strated that most children will readily handle a firearm, given the opportunity, regardless of how much previous gun-safety education they have received. [31][32][33] Likewise, previous gun-safety training for adults does not seem to have a positive correlation with likelihood of safe storage of firearms: a study of gun owners in 1 rural midwestern area found that respondents who had taken a firearmsafety course were twice as likely to keep guns loaded and unlocked as those who had not received such education. 24 Given the prevalence of firearms in American homes with children and the dangers of giving children ready access to firearms, understanding the factors that influence storage decisions is a critical part of preventing pediatric firearm injuries.…”
mentioning
confidence: 99%
“…9 However, few safety skills programs have been developed to teach children not to play with guns if they find them in the home or elsewhere. [10][11][12][13][14] Of these programs, the Eddie Eagle GunSafe Program, developed by the National Rifle Association, is the most recognized and implemented. The National Rifle Association estimates that the Eddie Eagle program has educated 15 million children since 1988, with an estimated 700 000 children receiving Eddie Eagle firearm injury prevention training each year.…”
mentioning
confidence: 99%